2006
DOI: 10.1039/b601794k
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic reduction of NO over supported silver catalysts—practical and mechanistic aspects

Abstract: Selective catalytic reduction of NO by hydrocarbons (HC-SCR) is one of the promising technologies for removal of NO in exhausts containing excess oxygen, such as diesel and lean burn gasoline engines. Supported Ag catalysts, especially Ag/Al2O3, are thought to be the promising candidates for use in diesel exhausts, as confirmed by several reports on engine bench tests. The HC-SCR performance of supported Ag catalysts is very sensitive to the reaction conditions, especially the type of hydrocarbons and the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
134
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 141 publications
5
134
0
1
Order By: Relevance
“…3,4,7,[13][14][15][16][17][18][19] Among the catalysts proposed for HC-SCR technology, zeolitic oxide catalysts are effective for NO x reduction, while their water tolerance has been little improved. 5 Noble metal catalysts such as Pt/Al 2 O 3 exhibit high deNO x activity in the low temperature range of 200-300 1C while exhibiting a narrow operation temperature window.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,7,[13][14][15][16][17][18][19] Among the catalysts proposed for HC-SCR technology, zeolitic oxide catalysts are effective for NO x reduction, while their water tolerance has been little improved. 5 Noble metal catalysts such as Pt/Al 2 O 3 exhibit high deNO x activity in the low temperature range of 200-300 1C while exhibiting a narrow operation temperature window.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the SCR of NO x by NH 3 or urea as a reductant, the SCR of NO x by hydrocarbon (HC) as a reductant can be a possible method to the removal of NO x from diesel and lean-burn gasoline engines. In recent studies, relatively durable and inexpensive alumina-supported silver catalysts (Ag/Al 2 O 3 ) have been considered to be a promising candidate for practical usage in the HC-SCR of NO x [2][3][4][5][6][7][8]. In our research into the HC-SCR of NO x over Ag/ Al 2 O 3 , we found a novel enolic surface species on Ag/ Al 2 O 3 [9] and proposed a new mechanism to explain the high-level efficiency of the SCR of NO x by ethanol over Ag/Al 2 O 3 [7,9,10], as shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Using C2H5OH as a reductant results in significantly higher NOx conversion when compared with C3H6, especially at low reaction temperatures [11]. Generally, the activation of the reductant is considered as the initial and key step in the HC-SCR process [3][4][5][6][19][20][21]. Ag sites are widely accepted as the activation spots for the reductant [22][23][24].…”
Section: Structures Of Intermediates Adsorbed Onto Ag-o-al Entitiesmentioning
confidence: 99%
“…The mechanisms of NOx reduction by hydrocarbons have been extensively explored [3][4][5][6][19][20][21]; the general reaction pathway is shown in Scheme 1. First, NO is oxidized to NO2 by O2, which results in the formation of surface nitrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation